019 Profiles of white matter degeneration in frontotemporal dementia. Issue 3 (9th February 2012) - Mahoney, C; Rossor, M N; Fox, N C; Warren, J D
Abstract : Introduction: Frontotemporal dementia (FTD) is a common cause of young onset dementia frequently presenting with progressive decline in behaviour and social cognitive skills. The neurobiological basis of FTD is complex with a spectrum of clinical, neuroanatomical and neuropathological associations. The concept of targeted destruction of a 'salience network' mediating social cognition has focused interest on connectivity-based approaches to understanding FTD. Here we describe white matter tractographic profiles in a cohort of patients with FTD. Methods: 15 consecutive patients with a clinical diagnosis of FTD and 20 age-matched healthy controls underwent diffusion tensor MRI. Patients were divided based on leading symptoms into 'behavioural variant' (bvFTD) and 'semantic-mnestic variant' (svFTD) clinical subgroups. Tractographic changes were compared with healthy controls and between FTD subgroups using tract-based spatial statistics. Results: Both FTD syndromic groups showed well-defined fractional anisotropy (FA), axial (DA) and radial (DR) diffusivity changes affecting white matter tracts previously implicated in aspects of social cognition. Compared to healthy controls both groups showed reduced FA and increased DR and DA in uncinate fasciculus, anterior thalamic radiation and corpus callosum; additional tractographic alterations were identified in association with svFTD (inferior longitudinal fasciculus) and bvFTD (cingulum). Discussion: Tractography can differentiate network signatures of clinical syndromes in the FTD spectrum, and warrants further evaluation as a candidate disease biomarker.